The "Rent-A-Womb" Boom: The Political Economy of India's Transnational Commercial Surrogacy Market - Masood, Surayya (My University, 2016)
Reproductive justice issues have been a heavily debated topic in the modern, globalized world. With the advent of many modern day reproductive technologies, there have been increasing concerns expressed within the realms of economics, politics, feminist studies and various other social sciences. Commercial surrogacy is one such reproductive issue that has become increasingly popular today and spans transnationally due to the existence of reproductive technologies. In lower income countries, like India, transnational commercial surrogacy has transformed into a booming business. However, throughout the history of reproductive politics, we have seen the commodification and fetishization of the human body, and we see the same occurring within the structures of transnational commercial surrogacy markets. For this research, we will examine the reductionist social and economic structures that have commodified female bodies, reducing their reproductive labor to that of an unskilled, abstract laborer working in a capitalist firm. This research aims to examine what kinds of exploitation takes place during the processes of transnational commercial surrogacy and will then argue whether the market should remain completely free, completely banned or should function with an enforcement of strict regulations. By providing a labor protection framework, this paper proposes that these markets should be strictly regulated by the state with greater emphasis on the protection of surrogate mothers, rather than be solely focused on the protection of rights intending parents and corporations.
Keywords: surrogacy; economics; exploitation; policy analysis; India